Mathematical Modeling and Optimization Studies by Artificial Neural Network, Genetic Algorithm and Response Surface Methodology: A Case of Ferric Sulfate–Catalyzed Esterification of Neem (Azadirachta indica) Seed Oil - Okpalaeke, Kelechi E.; Ibrahim, Taiwo H.; Latinwo, Lekan M.; Betiku, Eriola (Frontiers in Energy Research, 2020)
High free fatty acids (FFA) content in oils poses some challenges such as soap formation and difficulty in the separation of by-products in direct transesterification of oil to biodiesel, which is of environmental concern and also increases the cost of production. Thus, in this study, the ferric sulfate-catalyzed esterification of neem seed oil (NSO) with an FFA of 5.84% was investigated to reduce it to the recommended level of ≤ 1%. The esterification process was modeled using response surface methodology (RSM) and artificial neural network (ANN). The effect of the pertinent process input variables viz. methanol/oil molar ratio (10:1 – 30:1), ferric sulfate dosage (2 – 6 wt. %), and reaction time (30 – 90 min) and their interactions on the reduction of the FFA of the NSO were examined using Box Behnken design (BBD). While the process optimal condition for the reduction of the FFA content of the oil was established using RSM and ANN-genetic algorithm (ANN-GA). The results showed that the models developed described the process accurately with the coefficient of determination (R2) of 0.9656 and 0.9908 and the mean relative percentage deviation (MRPD) of 6.5 and 2.9% for RSM and ANN, respectively. The ANN-GA established the optimum reduction of FFA of 0.58% with methanol/oil molar ratio of 18.51, ferric sulfate dosage of 6 wt.%, and reaction time of 62.8 min as against the corresponding values of 0.62% FFA, 23.5, 5.03, and 75 min established by the RSM. Based on the statistics considered in the study, ANN and GA outperformed RSM in modeling and optimization of the NSO esterification process.